2020
DOI: 10.1002/sia.6764
|View full text |Cite
|
Sign up to set email alerts
|

Orientation‐dependent nanostructuring of titanium surfaces by low‐energy ion beam erosion

Abstract: Regular nanoscopic ripple and dot patterns are fabricated on poly-crystalline titanium samples by irradiation with 1.5 keV argon ions at normal incidence. The morphology of the nanostructures is investigated by scanning electron microscopy and scanning force microscopy. The ripple structures exhibit a saw-tooth cross-section profile. Electron backscatter diffraction experiments are performed to analyze the local grain structure. The study suggests a distinct correlation of the nanostructure morphology to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…For the latter reason, high temperature experiments have been also performed to reveal the grain size distribution and its eventual correlation with the pattern variation. Similar ripples on Ti surfaces produced under normal ion incidence have also been reported by Bauer et al [32], where the characteristic wavelength was suggested to be correlated with the local crystallographic orientation with respect to the ion beam. For i  65°, the morphology exhibits faceting, with the formation of terraces perpendicular to the direction of the ion beam.…”
Section: Surface Morphologysupporting
confidence: 83%
See 2 more Smart Citations
“…For the latter reason, high temperature experiments have been also performed to reveal the grain size distribution and its eventual correlation with the pattern variation. Similar ripples on Ti surfaces produced under normal ion incidence have also been reported by Bauer et al [32], where the characteristic wavelength was suggested to be correlated with the local crystallographic orientation with respect to the ion beam. For i  65°, the morphology exhibits faceting, with the formation of terraces perpendicular to the direction of the ion beam.…”
Section: Surface Morphologysupporting
confidence: 83%
“…As expected, the reviews discussed studies on the irradiation of Ti-based biomedical surfaces. For example, ion-beam etching and its impact on cell adhesion were reported for Ti-6Al-4V alloys [31,32]. The generation of ion-beam nanopatterns on pure Ti surfaces was also reported recently for low ion energies (< 2 keV) [32,33].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Over the last decade, many efforts have been carried out to either increase or decrease the wettability of PTFE surfaces using plasma etching and nanotexturing. [7] For this, various types of plasma discharges such as plasma-produced ion beam, [8,9] plasma jet, [10,11] capacitively coupled plasma (CCP), [12][13][14] inductively coupled plasma, [15] microwave plasma, [16] and so forth, were studied thoroughly. Different types of inert, as well as reactive gases like Ar, [9,[13][14][15] O 2 , [10,[16][17][18] Ar + O 2 , [8,19] He, [20] Air, [21] CF 4 , [22] and so forth, were introduced to physically and/or chemically modify the surface, eventually leading to the hydrophilic or superhydrophobic surface.…”
Section: Introductionmentioning
confidence: 99%
“…[7] For this, various types of plasma discharges such as plasma-produced ion beam, [8,9] plasma jet, [10,11] capacitively coupled plasma (CCP), [12][13][14] inductively coupled plasma, [15] microwave plasma, [16] and so forth, were studied thoroughly. Different types of inert, as well as reactive gases like Ar, [9,[13][14][15] O 2 , [10,[16][17][18] Ar + O 2 , [8,19] He, [20] Air, [21] CF 4 , [22] and so forth, were introduced to physically and/or chemically modify the surface, eventually leading to the hydrophilic or superhydrophobic surface. For instance, Kolská et al [17] used Ar CCP to modify the surface property of 25-µm-thin PTFE foils and found that the surface became superhydrophilic (WCA = 4°) after a treatment time of 600 s. A similar reduction in the contact angle after plasma treatment was observed by Carbone et al [16] while using atmospheric pressure Ar plasma.…”
Section: Introductionmentioning
confidence: 99%